ドーム フジ カンソク キョテン ニ オケル フウコウ ソクテイチ ノ エラー ト ホセイ - 平沢, 尚彦; ヒラサワ, ナオヒコ; Hirasawa, Naohiko (2000)
P(論文) 本論文では, 第38次南極地域観測隊によって1997年にドームふじ観測拠点で観測された地上風向データに複数の重大なエラーが含まれることを報告し, その特徴を記述した。最も重大なエラーは方位45度, 135度, 225度, 315度に向かって, 風向データが変移していることであった。補正方法の検討を通して, 1度の解像度を持つ測定データを同程度の解像度で補正することは不可能であることが分かり, 可能な最高の解像度として16方位に補正した。補正方法として, ドームふじ観測拠点で併行して観測していたAuto Weather Station (AWS)の風向を真値とし, AWS風向に合わせ込む経験的な方法を提案する。付録では補正方法に関する理論的な考察を行い, それに基づく一例として指数関数を利用した補正方法を検討するが, ここでは十分な補正結果が得られない。 Some kinds of error in surface wind direction data at Dome Fuji Station observed by the 38th Japanese Antarctic Research Expedition (JARE-38) in 1997 are reported. The most serious error is that the wind direction data was shifted toward azimuths of 45-, 135-, 225- and 315-degrees. However. data correction is possible since the error is systematic. For example. the data in the 0-∿90-degrees azimuth domain are shifted toward 45-degrees. As a result of examining the correction method. though it is impossible to correct the data with the same resolution of 1 degree that the observed data had, it is possible to correct it at the resolution of 16 sectors. Wind direction data of the Auto Weather Station (AWS) at Dome Fuji Station are regarded as true values in this correction process. An empirical method comparing with the AWS data was proposed here. In the appendix, theoretical discussion on the correction is given, and corrections using exponential functions are demonstrated, which however, do not work well. departmental bulletin paper